2000
DOI: 10.1017/s1355838200991787
|View full text |Cite
|
Sign up to set email alerts
|

The yeast antiviral proteins Ski2p, Ski3p, and Ski8p exist as a complex in vivo

Abstract: The yeast superkiller (SKI ) genes were originally identified from mutations allowing increased production of killer toxin encoded by M "killer" virus, a satellite of the dsRNA virus L-A. XRN1 (SKI1) encodes a cytoplasmic 59-exoribonuclease responsible for the majority of cytoplasmic RNA turnover, whereas SKI2, SKI3, and SKI8 are required for normal 39-degradation of mRNA and for repression of translation of poly(A) minus RNA. Ski2p is a putative RNA helicase, Ski3p is a tetratricopeptide repeat (TPR) protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
161
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(171 citation statements)
references
References 38 publications
5
161
1
4
Order By: Relevance
“…These data collectively suggest that hSKI, a protein complex that is required for 3Ј-to-5Ј RNA decay in yeast (Masison et al 1995;Brown et al 2000), associates with transcriptionally active genes via its interaction with the hPAF complex in the case of human cells. Notably, Exosome, the other complex that is required for RNA 3Ј-5Ј decay, was also reported to be associated with transcriptionally active genes via its interaction with the transcription elongation factor Spt6 (Andrulis et al 2002).…”
Section: Hski Complex Is Present At Transcriptionally Active Genes Wimentioning
confidence: 71%
See 3 more Smart Citations
“…These data collectively suggest that hSKI, a protein complex that is required for 3Ј-to-5Ј RNA decay in yeast (Masison et al 1995;Brown et al 2000), associates with transcriptionally active genes via its interaction with the hPAF complex in the case of human cells. Notably, Exosome, the other complex that is required for RNA 3Ј-5Ј decay, was also reported to be associated with transcriptionally active genes via its interaction with the transcription elongation factor Spt6 (Andrulis et al 2002).…”
Section: Hski Complex Is Present At Transcriptionally Active Genes Wimentioning
confidence: 71%
“…hSki8 is also a component of the human SKI (hSKI) complex. The yeast SKI complex and Exosome are both genetically required for 3Ј-to-5Ј mRNA decay (Ridley et al 1984;Masison et al 1995;Anderson and Parker 1998;Brown et al 2000;Araki et al 2001;Mitchell and Tollervey 2003). We found that hSKI localizes to transcriptionally active genes in an hPAF-dependent manner.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Ski2p, Ski3p, and Ski8p form a heterotrimeric complex that interacts with Ski7p and is required for nonstop decay (23,34,35). We therefore deleted the genes for each of these proteins from the [PSI ϩ ] strain and analyzed their effect on ade2-1 expression.…”
Section: [Psi ؉ ] and Premature Stop Codonsmentioning
confidence: 99%